THE MORAL VALUE OF “AMERICA THE BEAUTIFUL” - Bejo Sutrisno; Desi Rahmania Sari (STIBA IEC JAKARTA, 2017)
In coca cola ads America the beautiful, the writers analyze moral values on video Coca Cola. The writer used three video Coca-Cola ads America the beautiful, and some related books as the resource the data. The writer watched the video and then analyzed the data. From the analysis the writer conclude that some moral values are freedom, individualism, Achievement, tolerance, and the future. Coca cola indicates that America is so diverse nations, cultures, languages, and ethnics. It’s beautiful thing and Coca cola make this video to celebrate diverse culture in America. America is the place to learn how to mutual respect with others. And America is country that innovates because America is unique and capable changes in the surrounding environment and brings the profit and success